An updated overview of cyanidins for chemoprevention and cancer therapy - Posadino, Anna Maria; Giordo, Roberta; Ramli, Iman; Zayed, Hatem; Nasrallah, Gheyath K.; Wehbe, Zena; Eid, Ali H.; Gürer, Eda Sönmez; Kennedy, John F.; Aldahish, Afaf Ahmed; Calina, Daniela; Razis, Ahmad Faizal Abdull; et al. (Elsevier, 2023)
Anthocyanins are colored polyphenolic compounds that belong to the flavonoids family and are largely present in many vegetables and fruits. They have been used in traditional medicine in many cultures for a long time. The most common and abundant anthocyanins are those presenting an O-glycosylation at C-3 (C ring) of the flavonoid skeleton to form -O-²-glucoside derivatives. The present comprehensive review summarized recent data on the anticancer properties of cyanidings along with natural sources, phytochemical data, traditional medical applications, molecular mechanisms and recent nanostrategies to increase the bioavailability and anticancer effects of cyanidins. For this analysis, in vitro, in vivo and clinical studies published up to the year 2022 were sourced from scientific databases and search engines such as PubMed/Medline, Google scholar, Web of Science, Scopus, Wiley and TRIP database. Cyanidins antitumor properties are exerted during different stages of carcinogenesis and are based on a wide variety of biological activities. The data gathered and discussed in this review allows for affirming that cyanidins have relevant anticancer activity in vitro, in vivo and clinical studies. Future research should focus on studies that bring new data on improving the bioavailability of anthocyanins and on conducting detailed translational pharmacological studies to accurately establish the effective anticancer dose in humans as well as the correct route of administration.